Inter-ethnic Local Wisdom-culture Integration in Muslim Family Environment in Palu City - Muhammad Fath Azzajjad; Dewi Satria Ahmar; Iyan Nurdiyan Haris; Agus Nasir; Kasmudin Mustapa (CV. Media Digital Publikasi Indonesia, 2024)
Knowledge, the natural world, traditional medicine, and a strong belief system that emphasises unity are all components of local wisdom. Tribal coexistence in Palu City entails a number of protocols to protect the Kaili tribe's traditional knowledge. Cultural mingling occurs between the Bugis and Makassar tribes, who have long resided in Palu city. The urban centre of Palu City has been shaped and helped to flourish by the interplay of the Kaili, Bugis, and Makassar cultures. Families of Muslims from the three tribes coexist in socioreligious Despite their disparate religious customs, there is a great deal of religious concord among the tribes. In Palu City, Muslim groups coexist with other Muslim communities. Ethics, diversity, and tolerance are still upheld in balance and harmony. The Bugis and Makassar tribes have played a significant socioeconomic role in Palu city's growth.